Patterns of sexual behaviour and sexual healthcare needs among transgender individuals in Melbourne, Australia, 2011–2014. (29th September 2016) - Bellhouse, Clare; Walker, Sandra; Fairley, Christopher K; Vodstrcil, Lenka A; Bradshaw, Catriona S; Chen, Marcus Y; Chow, Eric P F
Abstract : Objective: Literature surrounding the healthcare needs of transgender individuals is limited in Australia. This study aimed to investigate the demographic characteristics, risk behaviours and HIV/STI positivity among male-to-female (MTF) and female-to-male (FTM) transgender individuals attending Melbourne Sexual Health Centre (MSHC), Australia, between 2011 and 2014. Method: A retrospective cohort analysis for 133 transgender individuals was conducted based on the first visit of individuals to MSHC during the study period. Demographic characteristics, sexual behaviours and HIV/STI positivity were examined. Results: The majority of transgender individuals were single or never married (74%; n=99). Almost half of the individuals (47%; n=62) had ever engaged in sex work during their lifetime. The median number of male sexual partners (MSP) reported in the last 3 months was 1 (IQR: 1–2) and with female sexual partners (FSP) was 2 (IQR: 1–4). For those who reported having sexual partners in the previous 3 months, always using condoms with MSP was 31% (n=22), and that with FSP was 18% (n=2). HIV/STI positivity during the study period was 7% (n=8) for chlamydia, 5% (n=6) for gonorrhoea, 5% (n=5) for syphilis and 1% (n=1) for HIV. Hormone use for reassignment was reported by 63% (n=90) of individuals and reassignment surgery was reported by 27% (n=29+6=35). Conclusions: Transgender individuals in this study were found to be a diverse group, with a history of sex work being a common feature. These findings indicate that transgender individuals' sexual healthcare needs differ substantially from those in other countries, including the US and Canada. Attention to differences in MTF and FTM transgender persons must be considered in healthcare settings in Australia.